Experiment study of an automatic guided vehicle robot - Vo Thu Ha; Than Thi Thuong; Vo Thanh Ha (Institute of Advanced Engineering and Science, 2023)
This paper presents the design and control of an autonomous robot-automation guided vehicle (AGV) with a load of 50 kg and a DC motor in theory and experiment. This robot has the function of transporting tools and equipment in the factory. This robot is designed and built control system including hardware and software. In which microcontroller type STM32F407VG is selected to control the primary system. The AGV robot is controlled to move according to the required trajectory. A PID controller controls the DC motor. The AGV robot moves precisely according to the routes set in the factory. At the same time, the AGV has good obstacle avoidance. The results of the proposed solution are proven through simulation and experiment.